Spontaneous morphological remodelling of the O-C1 joint after posterior fusion for occipitocervical dislocation. (3rd April 2022) - Iwai, Chizuo; Fushimi, Kazunari; Nozawa, Satoshi; Mitsuishi, Naofumi; Ogawa, Hiroyasu; Maeda, Masato; Kuramitsu, Norishige; Akiyama, Haruhiko
Abstract: Background: Traumatic occipitocervical dislocation (OCD) occurs due to fatal high-energy injury. Modern screw-based constructs enable successful reduction and stabilisation. In view of this, there are no previous reports on the spontaneous remodelling of the O-C1 joint after posterior fusion. We report the first case of postoperative spontaneous remodelling and stabilisation of the O-C1 joint after traumatic OCD. Case description: A 9-year-old girl suffered from traumatic OCD, accompanied by complete rupture of the O-C1-C2 ligamentous complex. Halo-vest fixation, and subsequently posterior fusion surgery from the occipital bone to C2, with autologous iliac crest bone graft and an allograft were performed. However, we could not achieve complete reduction of the O-C1 joint during surgery owing to extremely severe instability. Postoperative X-ray and computed tomography scan showed incomplete reduction of the O-C1 joint. Insufficient congruity of the O-C1 joint persisted. Afterwards, gradual spontaneous remodelling of the O-C1 joint occurred, both anteriorly and posteriorly 3 months postoperatively. Solid union was achieved 6 months postoperatively. Two years later, bilateral O-C1 joints in the patient were completely reformed and restabilised by incredible vigorous remodelling. Insufficient reduction and persisting poor joint congruence after surgery for OCD was probably restabilised by further spontaneous remodelling of articular morphology in such a young patient. Conclusions: Postoperative spontaneous remodelling of the O-C1 joint after posterior reconstruction for OCD may occur in young patients. Incomplete reduction of the O-C1 joint during surgery may be acceptable due to the possibility of postoperative bone remodelling and restabilisation.